2007
DOI: 10.1089/jmf.2006.213
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect ofTelfairia occidentalis(Fluted Pumpkin) in Rats Fed a Cholesterol-Rich Diet

Abstract: Telfairia occidentalis (fluted pumpkin) is one of the commonly consumed leafy vegetables in Nigeria. In order to justify its inclusion in herbal preparations in African traditional medicine, the possible hypolipidemic effect of this vegetable was investigated in rats fed a cholesterol-rich diet. The ability of Questran, a hypolipidemic drug, to attenuate hypercholesterolemia was also examined. Rats were fed with either a basal diet containing cholic acid (0.2%) or a supplemented diet with T. occidentalis at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…Several studies have indicated that carotenoid intake may reduce the risk of certain types of cancer, degenerative and cardiovascular diseases, cataracts and macular degeneration, which plays an important role in disease prevention. [5,6] Carotenoid pigments are sensitive to light, heat, oxygen and acid. [7] Pumpkins and pumpkin products are major sources of β-carotene and contribute significantly to carotenoid intake for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that carotenoid intake may reduce the risk of certain types of cancer, degenerative and cardiovascular diseases, cataracts and macular degeneration, which plays an important role in disease prevention. [5,6] Carotenoid pigments are sensitive to light, heat, oxygen and acid. [7] Pumpkins and pumpkin products are major sources of β-carotene and contribute significantly to carotenoid intake for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Blanching stops the enzyme action, sets the colour, and shortens the drying and dehydration time [10] . Telfairia occidentalis Hook f. (Curcubitaceae) (T. occidentalis) is a fluted pumpkin and is one of the green leafy vegetables widely consumed in Nigeria [14] . Leaves from this plant constitute an important ingredient in soup making since they are good sources of proteins, vitamins (B-complex), minerals, fatty acids (linoleic and oleic acids), and fibers [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, fluted pumpkin leaf extracts have been found to suppress or prevent production of free radicals and scavenge already produced free radicals, lower lipid peroxidation status and elevates antioxidant enzymes both in vitro and in vivo (Adaramoye et al, 2007;Kayode et al, 2009;Kayode et al, 2010). …”
Section: Resultsmentioning
confidence: 99%